2013
DOI: 10.1111/cch.12037
|View full text |Cite
|
Sign up to set email alerts
|

Measures of participation outcomes related to hand use for 2‐ to 12‐year‐old children with disabilities: a systematic review

Abstract: Many interventions have been used to improve children's hand-related impairments or hand skill performance in functional activities so as to promote life participation. There is thus a need to have suitable instruments assessing children's participation in life situations that specifically require hand use in order to support and evaluate such interventions. This systematic review investigated the availability of potential instruments that can be used to assess children's participation specifically in life sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 54 publications
0
18
0
3
Order By: Relevance
“…For two-group designs, was dropout balanced? (7) Considering the potential within the study design, were appropriate methods for controlling confounding variables and limiting potential biases used? 27 No Yes No Yes Unclear No Guli et al 28 No No No Yes Unclear No Hillier et al 23 Yes Yes No Yes Unclear Yes Sakzewski et al 24 Yes Yes No Yes Unclear Yes Scholtes et al 25 Yes Yes No Yes Unclear No Wuang et al 26 Yes…”
Section: Outcomes and Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…For two-group designs, was dropout balanced? (7) Considering the potential within the study design, were appropriate methods for controlling confounding variables and limiting potential biases used? 27 No Yes No Yes Unclear No Guli et al 28 No No No Yes Unclear No Hillier et al 23 Yes Yes No Yes Unclear Yes Sakzewski et al 24 Yes Yes No Yes Unclear Yes Scholtes et al 25 Yes Yes No Yes Unclear No Wuang et al 26 Yes…”
Section: Outcomes and Measuresmentioning
confidence: 99%
“…Enhancement of participation is often reported as the ultimate health and educational outcome and the primary goal of rehabilitation . Previous systematic literature reviews have examined the properties of available participation measurement tools, reported participation restrictions for people with disabilities, and identified supports and barriers to participation in people with disabilities . However, literature describing evidence‐based approaches to improving participation in people with disabilities is limited.…”
mentioning
confidence: 99%
“…Building on this theoretical work, the team conducted a comparative review identifying suitable instruments that assess children's participation in life situations that specifically require hand use (Chien, Rodger, Copley & McLaren, ). This theoretical work set the foundation for the development of a new assessment of hand‐use in children.…”
Section: Measurementmentioning
confidence: 99%
“…Revisiones sistemáticas previas han identificado escalas aplicables a poblaciones con patologías particulares, como por ejemplo, parálisis cerebral 23 o a grupos particulares de discapacidades 24,25,26 . Sin embargo, no existen revisiones sistemáticas que recomienden las escalas que puedan aplicarse simultáneamente a niños(as) y adolescentes con y sin discapacidad.…”
Section: Introductionunclassified